Development of a Web-Based Point of Sales System as a Financial Digitalization Solution for MSMEs - Elisa Daniati Edison; Nency Extise Putri; Arika Juwita Z; M. Ega. Darmawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in sustaining the national economy through their contribution to Gross Domestic Product (GDP), job creation, and the strengthening of local economies. However, amidst rapid technological advancements, many MSMEs still face significant operational challenges, particularly regarding financial management. Reliance on manual recording for sales and financial transactions increases the risk of data entry errors and operational inefficiencies. This study aims to design and develop an integrated web-based Point of Sales (POS) system to address these issues. The system was developed using the Waterfall Software Development Life Cycle (SDLC) model and implemented using the Laravel framework, supported by PHP, JavaScript, and MySQL. System evaluation was conducted through black-box testing to ensure functionality, alongside an analysis of the MSMEs' financial performance. The results demonstrate that the POS system substantially reduces transaction recording errors by automating sales calculations and centralizing data storage, thereby eliminating redundant data entry. This study provides a practical contribution to the digitalization of MSME transaction reporting, enhancing financial accuracy, operational transparency, and supporting effective strategic decision-making for business growth. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 5: Gender Equality